Determination of Groundwater Quality in Hatay Province, Turkey - KEMAL SANGUN, M.; GOKSEL OZDILEK, HASAN; ODEMIS, BERKANT (Asian Journal of Chemistry, 2010)
In this study, groundwater quality of Amik Plain and its surrounding areas is illustrated. A total of 59 groundwater wells located throughout Hatay Province were examined in this study. It was found that the water quality of wells is to a certain extent good for irrigational use; on the other hand, some wells, situated downstream Asi River after Antakya (Hatay Province center), have relatively low water quality even for irrigational use.